(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Spinal tuberculosis (STB), also known as Pott’s disease, is the most common form of skeletal tuberculosis and remains a significant cause of spinal deformity, neurological disability, and morbidity worldwide. Early diagnosis is often challenging because clinical manifestations are nonspecific and may overlap with other spinal disorders. Radiological evaluation, particularly magnetic resonance imaging (MRI), plays a crucial role in the detection and assessment of disease severity. Understanding the relationship between clinical presentation and radiological findings is essential for timely diagnosis and appropriate management. Objective: To systematically evaluate the clinical manifestations, radiological characteristics, and their correlation in patients with spinal tuberculosis through a comprehensive systematic review and meta-analysis. Methods: A systematic review and meta-analysis were conducted according to PRISMA guidelines. Electronic databases including PubMed, Scopus, Embase, Web of Science, Cochrane Library, and Google Scholar were searched for studies published between January 2000 and December 2025. Observational studies reporting clinical and radiological findings in patients with spinal tuberculosis were included. Data extraction and quality assessment were performed independently by two reviewers. Random-effects meta-analysis was used to calculate pooled prevalence estimates and odds ratios (ORs) with 95% confidence intervals (CIs). Results: Twenty-three studies comprising 5,482 patients were included in the final analysis. The pooled mean age was 41.8 years, and 59.1% of patients were male. Back pain was the most common clinical manifestation, occurring in 89.6% (95% CI: 84.2–93.3%) of patients, followed by constitutional symptoms in 63.4% (95% CI: 56.8–69.5%). Neurological deficits were present in 34.8% (95% CI: 28.7–41.4%) of patients. Thoracic spine involvement was the most frequent anatomical location (47.5%), followed by thoracolumbar (29.2%) and lumbar regions (18.4%). Vertebral body destruction (72.1%) and paravertebral abscess formation (67.3%) were the most common radiological findings. MRI demonstrated pooled sensitivity and specificity of 95.8% and 92.7%, respectively, for the diagnosis of spinal tuberculosis. Meta-analysis revealed a significant association between MRI evidence of spinal cord compression and neurological deficits (OR = 5.84, 95% CI: 3.72–9.16; p < 0.001). Kyphotic deformity and extensive vertebral destruction were also significantly associated with neurological impairment. Conclusion: Chronic back pain, thoracic vertebral involvement, vertebral destruction, and paravertebral abscess formation represent the predominant clinical and radiological features of spinal tuberculosis. MRI remains the gold-standard imaging modality owing to its high diagnostic accuracy and ability to detect neural compression and soft tissue involvement. Significant correlations between radiological severity and neurological deficits emphasize the importance of early clinico-radiological evaluation for preventing irreversible neurological complications and optimizing patient outcomes.